Why modern manuscripts matter - Sutherland, Kathryn (Oxford, UK : Oxford University Press, 2022)
In "Why Modern Manuscripts Matter," Andrew Piper delves into the intriguing world of literary manuscripts, exploring their multifaceted role in culture, commerce, and history. From the 18th century onward, manuscripts have captivated collectors, libraries, and scholars alike. Piper masterfully examines the reasons behind this fascination, highlighting the unique insights they offer into the creative process. By analyzing manuscripts as both tangible objects and repositories of meaning, he challenges conventional notions of authorship and the production of literary texts. Through a series of insightful case studies, including those of Samuel Johnson, Jane Austen, and Andy Warhol, Piper reveals how manuscripts can serve as fragments of art, commodities, and even waste. As digital technologies continue to reshape the literary landscape, Piper's work underscores the enduring significance of physical manuscripts. By considering their potential as both historical artifacts and contemporary art forms, he invites readers to reconsider the relationship between the written word and the material world.
Includes bibliographical references (p. 249-268) and index.
Keywords: Manuscript studies; Literary manuscripts; Material culture of literature; Cultural heritage; Book history; Digital humanities